What Makes Investors Trade? - Grinblatt, Mark; Keloharju, Matti (Journal of Finance, 2001)
ABSTRACT A unique data set allows us to monitor the buys, sells, and holds of individuals and institutions in the Finnish stock market on a daily basis. With this data set, we employ Logit regressions to identify the determinants of buying and selling activity over a two‐year period. We find evidence that investors are reluctant to realize losses, that they engage in tax‐loss selling activity, and that past returns and historical price patterns, such as being at a monthly high or low, affect trading. There also is modest evidence that life‐cycle trading plays a role in the pattern of buys and sells.